Nutrient management model for compensating spatial soil variability in rubber plantations in Amboori area - Anilkumar J R (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1989)
A study of the soils of rubber plantations in Amboori area has been undertaken to investigate the spatial variability of soil properties in those plantations with a view to relating it with the girth of the trees prior to tapping and to work out compensating models for nutrient management. Five plantations of three age groups viz. 1 – 2 years, 4 – 5 years and 6 – 7 years old but prior to the commencement of tapping were selected for this purpose. The plantations were having a slope of 20 – 300 and were planted with the rubber variety RR11 – 105. Soil samples collected from these plantations, from the previously fixed grid points separated by a lag distance (h) of 8 m along the slope, were analysed for the chemical properties such as pH, organic carbon, total and available nutrients. The leaf samples also taken, were analysed to know the nutrient contents in plant. Analysis of variance of the data to establish the variability, correlation and regression studies to relate the girth with nutrient variations in soil and plant, and computation of semi – variance Ý (h) for different lag distances for each nutrient to work out nutrient management models were undertaken. The study showed the existence of considerable spatical variability of soil properties in the plantations under study. Total nutrients such as total nitrogen, phosphorus and potassium were found to be spatially variable and significantly dependent on lag distances. However, three of the five plantations showed less impact of lag distances along the slope on the total nitrogen status of soil. While total calcium did not exhibit significant variations, total magnesium was found to possess spatial variation to some extent. A very significant spatial dependence characterised by an increase along the slope downwards with respect to available nitrogen, was an important observation of the study. Other available nutrients showed lesser degree of variations. Girth of trees when correlated with available nitrogen and organic carbon gave linear regression equations. Nutrient management models in terms of semi -variance were obtained for major nutrients of soil for compensating spatial variability of the nutrients. The models can be helpful in obliterating the effects of spatial variability of nutrients on crop growth. The model will be tested in the field at the Amboori tribal area Research Centre where extensive rubber plantations have been laid out.